2019
DOI: 10.1002/jmv.25639
|View full text |Cite
|
Sign up to set email alerts
|

Serotype‐specific differences in the laboratory parameters among hospitalized children with dengue and genetic diversity of dengue viruses circulating in Tamil Nadu, India during 2017

Abstract: In 2017, Tamil Nadu, a southern state, had the second highest number of dengue cases from India. In the present study, the serotype‐specific differences in the clinical manifestations and laboratory parameters among hospitalized children with dengue were investigated and molecular characterization of the circulating dengue virus (DENV) serotypes during 2017 in Tamil Nadu was performed. Eighty children with dengue‐like symptoms consecutively admitted to a tertiary care hospital and positive for DENV NS1 antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“… Rajesh and colleagues (2019) have reported high cases of hepatomegaly in DENV-4 during the 2017 dengue epidemic in Tamil Nadu, which is similar to our observation ( Tables 1 , S7 ). The γδ T cells of the liver are the major contributor of IL-17 during DENV infection ( Guabiraba and Ryffel, 2014 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“… Rajesh and colleagues (2019) have reported high cases of hepatomegaly in DENV-4 during the 2017 dengue epidemic in Tamil Nadu, which is similar to our observation ( Tables 1 , S7 ). The γδ T cells of the liver are the major contributor of IL-17 during DENV infection ( Guabiraba and Ryffel, 2014 ).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we have documented the co-circulation of all four serotypes in Madurai, Tamil Nadu during the 2017 outbreak. Though DENV-4, a rare serotype, has been isolated from various parts of India ( Cecilia et al., 2011 ; Dash et al., 2011 ; Kumar et al., 2013 ; Shrivastava et al., 2018 ; Rajesh et al., 2019 ), ours is the first report on DENV-4 as a dominant serotype during an outbreak after 1968 (49 years) in Tamil Nadu.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…One study has reported the absence of link between dengue severity and serotypes (Rao et al, 2020). Few other studies argue that dengue severity is associated with DENV serotype (Vaughn et al, 2000;Kalayanarooj and Nimmannitya, 2000;Endy et al, 2002;Nisalak et al, 2003;Kumaria, 2010;Vicente et al, 2016;Rajesh et al, 2020;Gupta et al, 2021). In particular DENV-3 serotype has been found to be associated with severe dengue in many studies (Kalayanarooj and Nimmannitya, 2000;Endy et al, 2002;Nisalak et al, 2003;Kumaria, 2010).…”
Section: Discussionmentioning
confidence: 99%